A review of Odontiinae (Lepidoptera: Crambidae) of Iran, with description of two new species - Alipanah, Helen; Nazari, Vazrick; Šumpich, Jan (Zootaxa, 2024)
The Odontiinae species of Iran are reviewed. Tegostoma pseudosarobiella Alipanah & Nazari sp. n. and T. tremewani Alipanah & Nazari sp. n. are newly described. Tegostoma moeschleri (Christoph, 1862) is considered as a senior synonym of T. uniforma Amsel, 1951 syn. n., T. lepidalis lepidalis (Herrich-Schäffer, 1851) as a senior synonym of T. lepidalis apurpurealis Amsel, 1970 syn. n., and Aeschremon belutschistanalis Amsel, 1959 as a senior synonym of Tegostoma marginalis Amsel, 1961 syn. n. The genus Autocharis Swinhoe, 1894 and five species, namely Aporodes dentifascialis Christoph in Romanoff, 1887, Cynaeda forsteri de Lattin, 1951, Aeschremon ochrealis Asselbergs, 2008, A. desertalis Asselbergs, 2008 and Autocharis fessalis (Swinhoe, 1887) are newly reported for the fauna of Iran. The redescription of female of Tegostoma confluentalis Hampson, 1913, male genitalia of Aeschremon belutschistanalis, and female genitalia of Epimetasia abbasalis Amsel, 1974 are presented. The hitherto unknown female of A. belutschistanalis and the hitherto unknown male of E. abbasalis are described and illustrated. The intraspecific variations of the species if present are discussed and additional new diagnostic characters to separate the closely related species are presented. Data on the geographical distribution of the Iranian species of this subfamily as well as their distribution maps are provided.